2008
DOI: 10.2215/cjn.05321107
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Plasmapheresis Decreases the Incidence of Acute Antibody-Mediated Rejection in Sensitized Patients with Strong Donor-Specific Antibodies

Abstract: Background and objectives: The objective of this study was to investigate the effects of desensitization protocols using intravenous Ig with or without plasmapheresis in patients with donor-specific anti-HLA antibodies on prevention of antibody-mediated rejection and downregulation of donor-specific antibodies.Design, setting, participants, & measurements: Thirty-five complement-dependent cytotoxicity T cell cross-match-negative but complement-dependent cytotoxicity B cell and/or flow cytometry cross-match-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 26 publications
2
62
1
Order By: Relevance
“…IVIG is crucial to the successful transplantation of highly sensitized renal transplant candidates. It has been used alone or in conjunction with plasmapheresis for desensitization (9,18,19). More recently, IVIG together with rituximab was able to achieve an 80% transplant rate in a population that would otherwise be unlikely to receive a transplant (17).…”
Section: Discussionmentioning
confidence: 99%
“…IVIG is crucial to the successful transplantation of highly sensitized renal transplant candidates. It has been used alone or in conjunction with plasmapheresis for desensitization (9,18,19). More recently, IVIG together with rituximab was able to achieve an 80% transplant rate in a population that would otherwise be unlikely to receive a transplant (17).…”
Section: Discussionmentioning
confidence: 99%
“…Akalin and colleagues found in their treatment protocols that AMR was observed only in patients with strong DSAs (MFI >6000 on Luminex® platform) [51]. Similarly Mayo clinic also found that the development of AMR was more likely in patients with strong DSAs and higher MCS on flow cytometry crossmatch [52].…”
Section: Patient Assessment: Histocompatibility Testingmentioning
confidence: 98%
“…The lowest rejection rates from Table 3 are seen in the data published by Mount Sinai using the addition of PP to IVIG/ATG pre-transplant conditioning protocols based on the intensity of DSA [51]. They studied a group of patients with CDC T cell negative crossmatch but T and/or B cell positive flow crossmatch.…”
Section: Modulation Of the Immune Response In Recipients With Crossmamentioning
confidence: 99%
“…Pre-transplant plasma exchange has been used in patients who are highly HLA sensitized to reduce donorspecific antibody levels and allow for successful renal transplantation, either from the deceased donor pool (by lowering PRA) or from a potential living donor (by eliminating a positive cross-match). In several studies of adult patients with high PRA, protocols including TPE (with low-dose intravenous immunoglobulin (IVIG) ± anti-CD20 therapy) have been shown to be superior to treatment with IVIG alone for desensitization with the goals of lowering donor specific antibodies (DSA) levels, reducing PRA, achieving a negative cross-match, avoiding post-operative AMR and prolonging graft survival [6][7][8]. A recent series of adult patients with end-stage renal disease (ESRD) demonstrated that patients who underwent desensitization with TPE and IVIG followed by living donor kidney transplantation had significantly improved survival than those who remained on dialysis and waited for an HLA-compatible deceased donor [9].…”
Section: Indications Prior To Renal Transplantationmentioning
confidence: 99%